Revisiting integrative motivation: Validation of International Posture among Malaysian undergraduates - Fatin Nabila Abd Razak; Vahid Nimehchisalem; Helen Tan; Geok Imm Lee; Ain Nadzimah Abdullah (Studies in English Language and Education, 2022)
Gardner’s (1985) in his socio-educational model introduced the variable of ‘integrativeness’ as a construct that focuses on English as a Second Language (ESL) learners’ attitudes towards the native English community. Later, Yashima (2002) proposed ‘international posture’ as an affective construct that re-examined ‘integrativeness’. Research conducted to reach a common operationalisation of ‘international posture’ is very limited. Hence, our objective in this study is to determine the level of each measurement construct under the affective variable of International Posture as well as to validate the measurement constructs of this variable among Malaysian undergraduates. In this quantitative study, 540 undergraduate students from a public university were selected. These students responded to a questionnaire that contained the four measurement constructs. For analysing the data, we used Partial Least Square-Structural Equation Modelling (PLS-SEM). Our results have proven that the International Posture among Malaysian undergraduates is high, and the measurement constructs of this variable are valid and can be operationalised in the Malaysian English language learning context. The scale validated in the study can contribute to future studies on this variable in the Malaysian English language learning context.